Analyse critique du processus de cogestion du parc national de Kahuzi-Biega en République Démocratique du Congo - Emery Mushagalusa Mudinga; Serge Ngendakumana; An Ansoms (VertigO)
For many years, the war has been considered as the major cause of the destruction of Kahuzi-Biega National Park (Eastern Democratic Republic of Congo). This paper recognizes the value of co-management of this protected area but show that other key factors such as political, structural, technical, demographic and economic aspects are also concerned in the failure of Park management